Systemic and Cerebral Effects of Physiotherapy in Mechanically Ventilated Subjects - Battaglini, Denise; Ciaravolo, Elena; Caiffa, Salvatore; Delpiano, Lara; Ball, Lorenzo; Vena, Antonio; Giacobbe, Daniele R; Bassetti, Matteo; Matta, Basil; Pelosi, Paolo; Robba, Chiara (Respiratory care, 2023)
Physiotherapy may result in better functional outcomes, shorter duration of delirium, and more ventilator-free days. The effects of physiotherapy on different subpopulations of mechanically ventilated patients on respiratory and cerebral function are still unclear. We evaluated the effect of physiotherapy on systemic gas exchange and hemodynamics as well as on cerebral oxygenation and hemodynamics in mechanically ventilated subjects with and without COVID-19 pneumonia. This was an observational study in critically ill subjects with and without COVID-19 who underwent protocolized physiotherapy (including respiratory and rehabilitation physiotherapy) and neuromonitoring of cerebral oxygenation and hemodynamics. P /F , P , hemodynamics (mean arterial pressure [MAP], mm Hg; heart rate, beats/min), and cerebral physiologic parameters (noninvasive intracranial pressure, cerebral perfusion pressure using transcranial Doppler, and cerebral oxygenation using near-infrared spectroscopy) were assessed before (T0) and immediately after physiotherapy (T1). Thirty-one subjects were included (16 with COVID-19 and 15 without COVID-19). Physiotherapy improved P /F in the overall population (T1 = 185 [108-259] mm Hg vs T0 = 160 [97-231] mm Hg, = .02) and in the subjects with COVID-19 (T1 = 119 [89-161] mm Hg vs T0 = 110 [81-154] mm Hg, = .02) and decreased the P in the COVID-19 group only (T1 = 40 [38-44] mm Hg vs T0 = 43 [38-47] mm Hg, = .03). Physiotherapy did not affect cerebral hemodynamics, whereas increased the arterial oxygen part of hemoglobin both in the overall population (T1 = 3.1% [-1.3 to 4.9] vs T0 = 1.1% [-1.8 to 2.6], = .007) and in the non-COVID-19 group (T1 = 3.7% [0.5-6.3] vs T0 = 0% [-2.2 to 2.8], = .02). Heart rate was higher after physiotherapy in the overall population (T1 = 87 [75-96] beats/min vs T0 = 78 [72-92] beats/min, = .044) and in the COVID-19 group (T1 = 87 [81-98] beats/min vs T0 = 77 [72-91] beats/min, = .01), whereas MAP increased in the COVID-19 group only (T1 = 87 [82-83] vs T0 = 83 [76-89], = .030). Protocolized physiotherapy improved gas exchange in subjects with COVID-19, whereas it improved cerebral oxygenation in non-COVID-19 subjects.